A Web-Based Tool for Collaboration and Transdisciplinary Learning Design in Communities of Practice - Vestergaard, Erik; Storm, Helle; Hansen, Gitte Riis (International Journal of Advanced Corporate Learning (iJAC), 2016)
idématch is a digital, web-based, and noncommercial platform developed by associate professors from University College Zealand, in cooperation with private enterprises, municipalities, and students. It is designed to bring students, public and private organizations, and citizens together, transforming ideas into practical solutions, through innovation, using collaborative and transdisciplinary learning designs contributing to new ways of welfare solutions for the Region of Zealand. The key focus is the contribution to innovation in partnership with the work field, students’ learning processes, and the development of analytical, experiential, experimental, and management competencies.